In the Scope of Logic, Methodology and Philosophy of Science
VIII, 362 p.
Keywords: This is the second of two volumes containing papers submitted by the invited speakers to the 11th international Congress of Logic, Methodology and Philosophy of Science, held in Cracow in 1999, under the auspices of the International Union of History and Philosophy of Science, Division of Logic, Methodology and Philosophy of Science. The invited speakers are the leading researchers and accordingly the book presents the current state of the intellectual discourse in the respective fields.